The Use of Hiking Sticks in the Mountains – Recommendation of the Medical Commission of the Union Internationale des Associations d’Alpinisme (UIAA) - Koukoutsi, Alexandra (Health Promotion & Physical Activity, 2020)
Many hikers, mountaineers and climbers use telescopic sticks because they may aid walking up/downhill and may also ease the strain on the spine and the lower extremity joints particularly the knees. The reductions during downhill walking with hiking poles are caused primarily by the forces applied to the hiking poles and by a change in posture to a more forward leaning position of the upper body.In order to have any benefits from telescopic sticks, they must be used with the correct technique: The sticks must be height-adjustable and have handles that are constructed in a way that the user’s hands, when pressing down, firm support is provided (or gained). It is of utmost importance to use the sticks as close as possible to the body’s line of fall. It has been shown that there is no significant difference in using one or two sticks when walking without a load, but when walking with a load, balance is significantly enhanced by using two hiking sticks rather than one. Previously a possible loss of the ability to maintain balance in rough or exposed terrain (e.g. small ridges) has been discussed (Berghold, F. personal communication). However, this could not be supported by studies. At high altitude or in cold environment the sticks should not be adjusted too long (the hands should be lower than the elbow when using the stick), because otherwise the circulation will be impaired and the user will get cold fingers in a very short time.